1986
DOI: 10.1128/iai.52.3.911-913.1986
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vivo and in vitro multiplication rates of Haemophilus influenzae type b

Abstract: A model of invasive Haemophilus influenzae type b disease in rats was used to compare the net in vivo and in vitro multiplication rates of this bacterium. In both the blood of rats and in vitro cultures (fresh rat blood or enriched broth) there was an exponential increase in the number of CFU per milliliter with calculated net mean generation times as follows: sham-operated rats, 82 ± 39 min (n = 5); asplenic rats, 34 ± 5 min (n = 13); broth, 26 ± 4 min (n = 12); rat blood, 24 + 1 min (n = 14). Thus, in vivo m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…the peritoneal cavity), followed by a translocation through lymphatic drainage into the systemic venous system via the thoracic duct and onward to relevant tissues, such as the spleen and kidneys where bacterial phagocytic clearance and filtration, respectively, take place 11 , 34 . Our findings are in accordance with previous studies indicating that E. coli , unlike bacteria such as Haemophilus influenzae , do not grow independently intravascularly 8 , 35 , 36 . Our data suggest that bacterial cells surviving in the bloodstream remain within the same state of growth as that of bacterial cells at the primary site of infection, without acceleration or significant deceleration; likely as the net result of constant influx- and kill-rate of bacteria.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…the peritoneal cavity), followed by a translocation through lymphatic drainage into the systemic venous system via the thoracic duct and onward to relevant tissues, such as the spleen and kidneys where bacterial phagocytic clearance and filtration, respectively, take place 11 , 34 . Our findings are in accordance with previous studies indicating that E. coli , unlike bacteria such as Haemophilus influenzae , do not grow independently intravascularly 8 , 35 , 36 . Our data suggest that bacterial cells surviving in the bloodstream remain within the same state of growth as that of bacterial cells at the primary site of infection, without acceleration or significant deceleration; likely as the net result of constant influx- and kill-rate of bacteria.…”
Section: Discussionsupporting
confidence: 94%
“…In a batch culture with a finite amount of nutrients, this curve is divided into well-defined growth phases 7 . However, bacterial growth dynamics in vivo are complex; growth rate is not solely a function of nutrient availability, but also of host immune-mediated clearance 8 11 . Applying bacterial count measurements to deduce an absolute bacterial growth rate in vivo is therefore not adequate, as this merely reflects the net change in bacterial population size.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of P2 expression significantly increased the generation time of Hib growing in vitro in broth and in normal rat serum. This decreased rate of growth would undoubtedly have a significant effect on the ability of Hib to grow in vivo, where it has been shown that growth of this pathogen is probably not limited by an inadequate supply of nutrients necessary for bacterial division (45). The significantly longer generation time of the Hib P2 mutant, as assessed in vitro, might augment the normal rate of clearance of this mutant by host defense mechanisms to such an extent that net multiplication of this mutant strain was prevented and efficient clearance resulted.…”
Section: Discussionmentioning
confidence: 99%